The Elaphidion Audinet-Serville of the Puerto Rican Bank: new species, distributions, taxonomic corrections, and a key to species (Coleoptera: Cerambycidae: Elaphidiini) - Ivie, Michael A.; Schwengel-Regala, Michelle L. (Zootaxa, 2007)
The six species of Elaphidion Audinet-Serville occurring in Puerto Rico and the Virgin Islands are keyed, illustrated and diagnosed. Elaphidion michelii Ivie NEW SPECIES (Puerto Rico) and Elaphidion mayesae Ivie NEW SPECIES (St. Thomas and Puerto Rico) are described. Previous records for E. pseudonomon Ivie for Puerto Rico are corrected to Elaphidion mayesae Ivie.